Determinants of Intraocular Pressure (IOP) of Glaucoma Patients at Felege Hiwot Referral Hospital, Bahir Dar, Ethiopia - Mitiku Wale Muluneh; Shewayiref Geremew Gebremichael (Advances in Public Health)
Background. Glaucoma is a leading cause of irreversible blindness in the world associated with characteristic damage to the optic nerve and patterns of visual field loss due to retinal ganglion cell degeneration. The main objective of this study was to investigate determinants for the variation of intraocular pressure of glaucoma patients under treatment at Felege Hiwot Referral Hospital, Bahir Dar, Ethiopia. Methods. A retrospective cohort study design was conducted on 328 randomly selected glaucoma patients in the ophthalmology clinic at the hospital under the follow-up period from January 2014 to December 2018. Glaucoma patients who have two and more than two visits in the study period were included in the study, but patients who are attending medications less than two visits were excluded from the study. A linear mixed-effects model for intraocular pressure change was used for data analysis. Result. The estimated coefficient of fixed effect intercept was 25.1829, which indicates that the average IOP of the patients was 25.1829 mmHg at baseline time by excluding all covariates in the model (p value <0.0001), age (β=0.07, 95%CI 0.03, 0.11), urban residence (β = −1.60, 95%CI −2.84, −0.36), family history of glaucoma (β = 4.90, 95%CI 3.38–6.43), timolol and pilocarpine medication (β = −2.02, 95%CI −4.01, −0.03), cup-disk ratio >0.7 (β = 2.60, 95% CI 1.24–3.96), and follow-up time (β = −0.34, 95%CI −0.47, −0.21) were significantly associated with intraocular pressure of glaucoma patients. Conclusion. The predictor age, residence, family history of glaucoma, type of medication, cup-disk ratio, and follow-up time were significantly associated with the intraocular pressure of glaucoma patients. Therefore, healthcare providers give more attention and prioritize those identified factors and give frequent counseling about reducing intraocular pressure of glaucoma patients.